2017
DOI: 10.1097/md.0000000000007254
|View full text |Cite
|
Sign up to set email alerts
|

Cross-cultural adaption and validation of the Persian version of the SWAL-QOL

Abstract: The aim of this study was to translate and cross-culturally adapt the swallowing quality-of-life questionnaire (SWAL-QOL) to Persian language and to determine validity and reliability of the Persian version of the swallow quality-of-life questionnaire (PSWAL-QOL) in the patients with oropharyngeal dysphagia.The cross-sectional survey was designed to translate and cross-culturally adapt SWAL-QOL to Persian language following steps recommended in guideline. A total of 142 patients with dysphagia (mean age = 56.7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 19 publications
1
5
0
Order By: Relevance
“…This means that the items in each scale are homogenous and evaluate different features of alike characteristics. These findings are similar to the results found in the original English version [9], Swedish [16], and Persian versions [17] of SWAL-QOL, although these studies showed that eating duration and sleep were just below the standard cutoff point.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…This means that the items in each scale are homogenous and evaluate different features of alike characteristics. These findings are similar to the results found in the original English version [9], Swedish [16], and Persian versions [17] of SWAL-QOL, although these studies showed that eating duration and sleep were just below the standard cutoff point.…”
Section: Discussionsupporting
confidence: 89%
“…SWAL-QOL is a self-report questionnaire used to evaluate the impact of swallowing problems on QOL [9]. Its original version was translated to different languages and has been used as a gold standard tool in various dysphagia researches tackling QOL aspects [13][14][15][16][17][18][19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 20 , 30 ] The validation of Chinese, Dutch, Swedish, Persian, and Korean linguistic versions of the SWAL-QOL have also been proved. [ 6 , 7 , 23 , 31 , 32 ] The Korean version of the SWAL-QOL as a tool to evaluate a patient's quality of life related to dysphagia in stroke patients was used in this study.…”
Section: Discussionmentioning
confidence: 99%
“…2,3 Dysphagia, which can lead to problems such as pneumonia, aspiration, malnutrition, and even death, is a significant symptom in many neurological diseases such as stroke, multiple sclerosis, Parkinson disease (PD), dementia, and head and neck cancer (HNC). 1,4 Furthermore, this disorder can lead to long-term social and functional limitations, mood disorders such as anxiety and depression, nutritional deficiencies, and a decreased quality of life (QOL). [5][6][7] Head and neck cancer is a general term that encompasses cancer in the oral cavity, the larynx, the pharynx, the salivary glands, the thyroid, the nasal sinuses, and lymph nodes in the neck.…”
Section: Introductionmentioning
confidence: 99%